PROTECTION OF PRIVATE DATA CONSUMERS P2P LENDING AS PART OF E-COMMERCE BUSINESS IN INDONESIA - Winarso, Teguh; Disemadi, Hari Sutra; Prananingtyas, Paramita (Tadulako University, 2020)
The use of information technology in Indonesia has increased significantly and has affected the aspects of human life. One of them is the presence of e-commerce platform money lending rather than financial technology in the form of peer to peer lending (P2P Lending). P2P Lending is the practice or method of giving money to individuals or businesses and vice versa, applying for loans to lenders, which connects lenders with borrowers or investors online. However, the problem currently faced is the protection of P2P Lending consumers' data. Therefore, this normative legal research aims to find out and examine the protection of personal data of P2P Lending consumers as part of the e-commerce business in Indonesia. This research shows that the implementation of P2P Lending is regulated in POJK No. 77/POJK.01/2016 and PBI No.19/12/PBI/2017. These two rules were formed aiming to ensure the implementation of P2P Lending and be able to keep abreast of financial technology very quickly. Then the protection of P2P Lending consumer private data has been set in the ITE Law. The presence of the ITE Law aims to protect private data in P2P Lending activities as part of an e-commerce business. But the ITE Law does not yet contain specific data protection rules.